A potential role for the paraventricular nucleus of the thalamus in mediating individual variation in Pavlovian conditioned responses - Haight, Joshua L.; Flagel, Shelly B. (Frontiers in Behavioral Neuroscience, 2014)
There is ample evidence to suggest that the paraventricular nucleus of the thalamus (PVT) mediates cue-reward learning, especially as it relates to drug-seeking behavior. However, its exact role in these complex processes remains unknown. Here we will present and discuss data from our own laboratory which suggests that the PVT plays a role in multiple forms of stimulus-reward learning, and does so via distinct neurobiological systems. Using an animal model that captures individual variation in response to reward-associated cues, we are able to parse the incentive from the predictive properties of reward cues and to elucidate the neural circuitry underlying these different forms of cue-reward learning. When rats are exposed to a classical Pavlovian conditioning paradigm, wherein a cue predicts food reward, some rats, termed sign-trackers, approach and manipulate the cue upon its presentation. This behavior is indicative of attributing incentive salience to the cue. That is, the cue gains excessive control over behavior for sign-trackers. In contrast, other rats, termed goal-trackers, treat the cue as a mere predictor, and upon its presentation go to the location of reward delivery. Based on our own data utilizing this model, we hypothesize that the PVT represents a common node, but differentially regulates the sign- vs. goal-tracking response. We postulate that the PVT regulates sign-tracking behavior, or the attribution of incentive salience, via subcortical, dopamine-dependent mechanisms. In contrast, we propose that goal-tracking behavior, or the attribution of predictive value, is the product of “top-down” glutamatergic processing between the prelimbic cortex (PrL) and the PVT. Together, data from our laboratory and others support a role for the PVT in cue-motivated behaviors and suggest that it may be an important locus within the neural circuitry that goes awry in addiction and related disorders.